Protein engineering strategy for the stabilization of HIV-1 α-helical peptides - Tennyson, Rachel Lee, author; Kennan, Alan, advisor; Ackerson, Christopher, committee member; Snow, Christopher, committee member; Gustafson, Daniel, committee member (Colorado State University. Libraries, 2019)
Many disease-relevant protein-protein interactions (PPIs) contain an alpha helix and helical binding cleft at their interface. Disruption of these interactions with helical peptide mimics is a validated therapeutic strategy. However, short peptides typically do not fold into stable helices, which significantly lowers their in vivo stability. Researches have reported methods for helical peptide stabilization but, these approaches rely on laborious, and often expensive, chemical synthesis and purification. The research I have preformed aims to stabilize disease-relevant helices through protein engineering. In contrast to chemically constrained helical peptides, a protein can be expressed in a cellular system on a much larger scale. Recently, we reported a new strategy termed "helix-grafted display" that overcomes the traditional hurdles of helical mimics and applied it to the challenge of suppressing HIV entry. Our helix grafted proteins, potently inhibits formation of the extracellular PPI involving C-peptide helix, and HIV gp41 N-peptide trimer, as tested in HIV CD4+ cells. Further optimization of the helical sequence by yeast display yielded new proteins that suppress HIV-1 entry and express substantially better in E. coli. Furthermore, fusion proteins designed to improve the serum stability of these helix grafted proteins have been made that potently suppress HIV-1 entry. Collectively, I report a potential cocktail of evolved HIV-1 entry inhibitors that are functional against an Enfuvirtide-resistant strain and are designed for serum stabilities that rival current monoclonal antibody drugs.